Exploring grafting to propagate and conserve Garcinia kola a vulnerable species in Côte d’Ivoire: Vegetative propagation of Garcinia kola by grafting - DAO, Jonas Patrick; Kouakou, Camille; Cherif, Mamadou; Yeo, Katienapariga Tayourou; Guinagui, N’doua Bertrand; Mbo, Kacou Antoine Alban; KOUAKOU, Kouakou Laurent (Advances in Horticultural Science, 2025)
Garcinia kola, a high-socioeconomic and multipurpose fruit tree, has been shown to have a low germination and long juvenile phase, which limit its cultivation initiative. Our study aimed to determine successful G. kola grafting conditions to promote its cultivation. So trials were carried out in June and August, testing four grafting methods: simple whip, top cleft, side cleft, and chip budding made on 12- and 36-month-old rootstock. The grafts were unwrapped at 15, 22, and 29 days after grafting. The results showed that the month of June is the favorable period for G. kola grafting. The best grafting success was observed with the chip budding and top cleft grafting methods applied on the 36- and 12-month-old rootstocks, respectively. The graft unwrapping time at 29 days after grafting promotes the best grafting success. The combined effect showed that the best graft success rate was recorded in June on 36-month-old rootstock (43.33%) with the chip budding and side cleft grafting method and 83.33% for the graft made on 12-month-old rootstock with the top cleft grafting method, respectively. This study is an important step for good plant material for domestication and cultivation of this resource.